KLK5 induces shedding of DPP4 from circulatory Th17 cells in type 2 diabetes - Titli Nargis; Krishna Kumar; Amrit Raj Ghosh; Amit Sharma; Dipayan Rudra; Debrup Sen; Saikat Chakrabarti; Satinath Mukhopadhyay; Dipyaman Ganguly; Partha Chakrabarti (Elsevier, 2017)
Objective: Increasing plasma levels and activity of dipeptidyl peptidase-4 (DPP4 or CD26) are associated with rapid progression of metabolic syndrome to overt type 2 diabetes mellitus (T2DM). While DPP4 inhibitors are increasingly used as anti-hyperglycemic agents, the reason for the increase in plasma DPP4 activity in T2DM patients remains elusive. Methods: We looked into the source of plasma DPP4 activity in a cohort of 135 treatment naive nonobese (BMI < 30) T2DM patients. A wide array of ex vivo, in vitro, and in silico methods were employed to study enzyme activity, gene expression, subcellular localization, protease identification, surface expression, and protein-protein interactions. Results: We show that circulating immune cells, particularly CD4+ T cells, served as an important source for the increase in plasma DPP4 activity in T2DM. Moreover, we found kallikrein-related peptidase 5 (KLK5) as the enzyme responsible for cleaving DPP4 from the cell surface by directly interacting with the extracellular loop. Expression and secretion of KLK5 is induced in CD4+ T cells of T2DM patients. In addition, KLK5 shed DPP4 from circulating CD4+ T helper (Th)17 cells and shed it into the plasma of T2DM patients. Similar cleavage and shedding activities were not seen in controls. Conclusions: Our study provides mechanistic insights into the molecular interaction between KLK5 and DPP4 as well as CD4+ T cell derived KLK5 mediated enzymatic cleavage of DPP4 from cell surface. Thus, our study uncovers a hitherto unknown cellular source and mechanism behind enhanced plasma DPP4 activity in T2DM.